Teachers' Conceptions of Assessment: A Global Phenomenon or a Global Localism - Brown, Gavin T. L.; Gebril, Atta; Michaelides, Michalis P. (Frontiers in Education, 2019)
How teachers conceive of the nature and purpose of assessment matters to the implementation of classroom assessment and the preparation of students for high-stakes external examinations or qualifications. It is highly likely that teacher beliefs arise from the historical, cultural, social, and policy contexts within which teachers operate. Hence, it may be that there is not a globally homogeneous construct of teacher conceptions of assessment. Instead, it is possible that a statistical model of teacher conceptions of assessment will always be a local expression. Thus, the objective of this study was to determine whether any of the published models of teacher assessment conceptions could be generalised across data sets from multiple jurisdictions. Research originating in New Zealand with the Teacher Conceptions of Assessment self-report inventory has been replicated in multiple locations and languages (i.e., English in New Zealand, Queensland, Hong Kong, and India; Greek in Cyprus; Arabic in Egypt; Spanish in Spain, Ecuador) and at different levels of instructional contexts (Primary, Secondary, Senior Secondary, and Teacher Education). This study conducts secondary data analyses in which eight previously published models of teacher conceptions of assessment were systematically compared across 11 available data sets. Nested multi-group confirmatory factor analysis (using Amos v25) was carried out to establish sequentially configural, metric, and scalar equivalence between models. Results indicate that only one model (i.e., India) had configural invariance across all 11 data sets and this did not achieve metric equivalence. These results indicate that while the inventory can be used cross-culturally after localized adaptations, there is indeed no single global model. Context, culture, and local factors shape teacher conceptions of assessment.